Determinan Stunting Balita di Wilayah Kerja Puskesmas Moutong, Kabupaten Parigi Moutong, Sulawesi Tengah: Determinants of Toddler Stunting in the Working Area of ​​the Moutong Health Center, Parigi Moutong Regency, Central Sulawesi - Taqwin Taqwin; Anna Veronica Pont; Yuyun Iskandar (Poltekkes Kemenkes Palu, 2023)
Introduction: The causes of stunting are maternal nutritional status, non-exclusive breastfeeding, low birth weight, and family income. This study aims to analyze the determinants of stunting among toddlers at Moutong Health Center in 2020. The research method used was cross-sectional. The study was conducted from March 3 to March 21, 2020, at Moutong Health Center, Parigi Moutong, Central Sulawesi. The data used in this study were secondary data from 2020. The sample size consisted of 222 toddler respondents. Simple random sampling technique was employed. Data analysis was performed using chi-square test and odds ratio. The results of the study showed that the highest prevalence of stunting was found among pregnant women with low nutritional status (61.1%), non-exclusive breastfeeding (59.6%), low birth weight (55.9%), and low family income (68.2%). Chi-square test indicated that all variables had significant values (<0.05). Multivariate analysis showed an odds ratio of 4.5 for low birth weight and stunting. In conclusion, this study found that low birth weight had a 4.5 times higher risk of stunting. It is recommended that healthcare professionals conduct education, prevention, and early detection of stunting, monitor the provision of maternal and child nutrition programs to pregnant women and toddlers, and provide assistance to low-income families or those who are unable to afford proper nutrition.